The Quest for Entrepreneurial Universities in East Asia - Mok, Ka Ho.; SpringerLink (Online service) (New York : Palgrave Macmillan US : Imprint: Palgrave Macmillan, 2013)
With the rise of the knowledge economy, universities are under pressure to embrace not just their traditional missions of teaching and research but a third mission of serving economic and social development. This book examines the major strategies that governments in East Asia have adopted to promote this kind of innovation in the education sector.
Keywords: Education; International education; Comparative education; School management and organization; School administration; Educational sociology; Higher education; Development economics; Asia -- Economic conditions; Education and sociology; Sociology, Educational; Education; Higher Education; International and Comparative Education; Sociology of Education; Asian Economics; Administration, Organization and Leadership; Development Economics